2015
DOI: 10.1128/aac.01473-15
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a New cfr -Like Gene, cfr (B), in Enterococcus faecium Isolates Recovered from Human Specimens in the United States as Part of the SENTRY Antimicrobial Surveillance Program

Abstract: Two linezolid-resistant Enterococcus faecium isolates (MICs, 8 g/ml) from unique patients of a medical center in New Orleans were included in this study. Isolates were initially investigated for the presence of mutations in the V domain of 23S rRNA genes and L3, L4, and L22 ribosomal proteins, as well as cfr. Isolates were subjected to pulsed-field gel electrophoresis (just one band difference), and one representative strain was submitted to whole-genome sequencing. Gene location was also determined by hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
96
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 37 publications
1
96
1
1
Order By: Relevance
“…The cfr gene was first discovered in a bovine Staphylococcus sciuri strain and was later reported in various Staphylococcus species (10)(11)(12). Recently, a cfr homologue, cfr(B), was discovered in Clostridium difficile and Enterococcus faecium (13,14). Besides resistance to oxazolidinones, the cfr gene also mediates cross-resistance to phenicols, lincosamides, pleuromutilins, and streptogramin A antibiotics (15).…”
mentioning
confidence: 99%
“…The cfr gene was first discovered in a bovine Staphylococcus sciuri strain and was later reported in various Staphylococcus species (10)(11)(12). Recently, a cfr homologue, cfr(B), was discovered in Clostridium difficile and Enterococcus faecium (13,14). Besides resistance to oxazolidinones, the cfr gene also mediates cross-resistance to phenicols, lincosamides, pleuromutilins, and streptogramin A antibiotics (15).…”
mentioning
confidence: 99%
“…The clinical data have been supported by the LEADER Surveillance Program, established in 2004 to detect emerging antimicrobial resistance among Gram-positive cocci (GPC) in the United States (5). For 12 consecutive years, this program has provided yearly information regarding linezolid resistance mechanisms, including the identification of new and emerging mechanisms (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Resistance development appeared early in clinical use in staphylococci and enterococci through ribosomal mutation in the 23S rRNA (6,13). Subsequently, an rRNA methyltransferase was identified that conferred resistance to linezolid and other antimicrobial agents (7,9,14,15; see https://doi-org .ezproxy.library.tufts.edu/10.1093/jac/dkx023). This cfr rRNA methyltransferase has the potential to mobilize, and, although it has been detected among an expanding number of GPC, it is still not the dominant mechanism of linezolid resistance among clinical GPC (5).…”
mentioning
confidence: 99%
“…Besides these mutations, the cfr gene, the first reported transferable oxazolidinone resistance gene, encodes a methyltransferase that modifies the 23S rRNA at position A2503 that mediates the resistance not only to linezolid but also to phenicols, lincosamides, pleuromutilins, and streptogramin A. Moreover, a cfr variant gene, designated cfr(B) (5,6), and the second transferable oxazolidinone resistance gene optrA have been identified (7).…”
mentioning
confidence: 99%
“…MICs were determined by the 2-fold agar dilution method according to the recommendations of the CLSI, and the reference strain E. faecalis ATCC 29212 served as a quality control (12). Moreover, all of the optrA-positive isolates were screened for cfr and cfr(B), and isolates with linezolid resistance (MIC of Ն8 mg/ liter) were also screened for the presence of the 23S rRNA mutation and ribosomal protein (L3/L4) mutation as previously described (5,7,13).…”
mentioning
confidence: 99%